Characterization of two bacterial tyrosinases from the halophilic bacterium Hahella sp. CCB MM4 relevant for phenolic compounds oxidation in wetlands - Gustavo deAlmeida Santos; Andrea N. B. Englund; Eirin L. Dalleywater; Åsmund Kjendseth Røhr (FEBS Open Bio)
Tyrosinases (TYRs) are type‐3 copper proteins that are widely distributed in nature. They can hydroxylate and oxidize phenolic molecules and are mostly known for producing melanins that confer protection against photo induced damage. TYRs are also thought to play an important role in the ‘latch mechanism’, where high concentrations of phenolic compounds inhibit oxidative decomposition of organic biomass and subsequent CO2 release, especially relevant in wetland environments. In the present study, we describe two TYRs, HcTyr1 and HcTyr2, from halophilic bacterium Hahella sp. CCB MM4 previously isolated at Matang mangrove forest in Perak, Malaysia. The structure of HcTyr1 was determined by X‐ray crystallography at a resolution of 1.9 Å and represents an uncharacterized group of prokaryotic TYRs as demonstrated by a sequence similarity network analysis. The genes encoding the enzymes were cloned, expressed, purified and thoroughly characterized by biochemical methods. HcTyr1 was able to self‐cleave its lid‐domain (LID) in a protease independent manner, whereas the LID of HcTyr2 was essential for activity and stability. Both enzymes showed variable activity in the presence of different metals, surfactants and NaCl, and were able to oxidize lignin constituents. The high salinity tolerance of HcTyr1 indicates that the enzyme can be an efficient catalyst in the habitat of the host.